Pengaruh tingkat pendidikan, struktur umur dan kematian bayi terhadap fertilitas di Kota Pekanbaru - Oktavia, Windi Yohana; Putro, Tri Sukirno; Sari, Lapeti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The research was conducted Pekanbaru City in May and June 2014. The purpose of research to find out influence of education level, age structure and infant mortality to fertility. This research using primer data and analysis of data used is deskriptive method. Population sampling of this research is reproductive age couple of wife at district of Tampan, Bukit Raya, Marpoyan Damai, and Tenayan Raya as much 86.145 RAC (Reproductive Age Couple). Sample in this research using Slovin formula as much 100 reproductive age couple of wife, while using simple random sampling technique. Conclution of the research that 48 respondent were in senior high school level with at most 2 fertility, and 26 respondent were in academy at most 1 fertility, in the meantime respondent with low education or primary school and middle school at most 3-4 fertility. This is show that aducation level RAC of wife influence fertility. Age structure RAC of wife showed the age of the first marriege. Majority of respondent marriege at the age of 20-24 years old as much 58 respondent. Respondent marriege at the age of < 20 and 20-29 years old fertility there’s a lot, meanwhile respondent marriege at the age of > 30 nothing 3 or 4 fertility. This is show that age structure RAC of wife showed the age of the first marriege influence fertility. Of 100 this respondent only 10 respondent have infant mortality and respondent having 2 until > 4 fertility. Nothing of respondent having fertility > 4 with 2 infant mortality. This is show that infant mortality influence to fertility.Keywords: Education level, age stucture, infant mortality and fertility